Hematologic malignancy in tanker crewmembers: A case‐referent study among male Swedish seafarers - Forsell, Karl; Björ, Ove; Järvholm, Bengt; Nilsson, Ralph; Andersson, Eva (American journal of industrial medicine, 2020)
Background Work on Swedish petroleum tankers before the late 1980s has been associated with an increased risk of hematologic malignancy (HM). Since then, ship modernizations have decreased occupational exposure to gases, including the carcinogen benzene. We explored the risk of HMs in Swedish seafarers who had worked on newer types of tankers. Methods A case‐referent study in male seafarers from a cohort of all Swedish seafarers was set up by record linkage with the Swedish Cancer Registry using the subjects' personal identification number. For each case (N = 315), five referents were randomly chosen from within the cohort, matched by birth year and three different periods of first sea service (<1985, 1985‐1991, and ≥1992). Information on the type of ship and dates of service was retrieved from the Swedish Seafarers' Registry. Odds ratios (OR) were calculated by conditional logistic regression together with 95% confidence intervals (CI). Results The OR of HM was 1.07 (95% CI, 0.80‐1.42) for work on tankers. In seafarers that had started to work on tankers ≥1985, the OR was 0.85 (95% CI, 0.50‐1.43). For those who started to work on tankers before 1985, the OR was 1.17 (95% CI, 0.84‐1.21) and 1.32 (95% CI, 0.86‐2.03) if the cumulative time on tankers exceeded 5 years of service. In this last group, the OR of multiple myeloma was 5.39 (95% CI, 1.11‐26.1). Conclusion Although limited by crude exposure contrast and a short follow‐up, work on tankers after 1985 was not associated with an increased risk of HM among Swedish seafarers.